Skrining Fitokimia dan Optimasi Aktivitas Anti-Ultraviolet Emulsi Ekstrak Etanol Suruhan (Peperomia pellucida) Secara In Vitro - Sabrina Faradiba Ashibna; Intan Nurkholidah (Pusat Riset dan Inovasi Nasional, 2023)
The Suruhan plant (Peperomia pelluida) has many benefits that cannot be separated from the compounds contained in the suruhan plant. Traditionally, the suruhan plant is used by the people of Kalimantan as a cold powder, so in this research a phytochemical screening was carried out and the SPF value of the suruhan extract emulsion was tested. The results showed that the extract contained flavonoids, alkaloids, phenolics and terpenoids. Testing the SPF values ​​obtained 5 formulas that had anti-ultraviolet activity in the medium and low categories with the highest SPF value of 31.48.